Spectroscopy of a topological phase - Kamfor, Michael; Dusuel, Sebastien; Vidal, Julien; Schmidt, Kai Phillip (Physical Review B, 2014)
Dynamical correlation functions of the toric code in a uniform magnetic field are studied inside the topological phase, in the small-field limit. Such an experimentally measurable quantity displays rich field-dependent features that can be understood via the interplay of the kinetics and the interaction of the anyonic excitations. In particular, it is sensitive to the two-quasiparticle bound states that are present in the spectrum for a wide range of magnetic fields. Interestingly, such collective modes can even constitute the lowest-energy excitations of the system.